Analisis Desain Arsitektur Masjid di Pulau Jawa dan Masjid di Pulau Sumatera sebagai Bangunan Evakuasi Bencana Banjir di Indonesia - Hotimah, Oot; Awalliyah, Syahru Putri; Nurjanah, Ula (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Indonesia, as an archipelagic country located in the equatorial region, is faced with a high risk of natural disasters, especially floods, due to its volcanic location and the intersection of three main tectonic plates. In this context, this research aims to analyze the potential of mosques in DKI Jakarta and the Batanghari River basin as flood disaster evacuation buildings. Using a descriptive-analytical study method with a combined approach between online and field observations, as well as data from the official government website, this research evaluates mosques based on the criteria of floor height, availability of the 2nd floor, and other supporting facilities. The results show that there is significant variation in mosque architectural design and facility availability, with some mosques having potential evacuation buildings while others require significant modification to increase their functionality in the face of flood disasters. This research suggests the need to modify the mosque design, including increasing the floor height and adding second-floor facilities and stairs, to strengthen the role of the mosque as an effective evacuation site.